Investigation of constituent determinants of financial inclusion: evidence from Mauritania - Sidi, Mohamed Khalifa; Kassim, Salina (Inderscience Enterprises Ltd., 2023)
It has been globally acknowledged that financial inclusion is one of the most important methods to achieve sustainable development and reduce the incidence of poverty in society. Unfortunately, more than 50% of the adults in the low-income countries are still financially excluded. This paper empirically examines the potential determinants of accessibility to financial services among the Mauritanians. In methodology, a total of 583 self-administered questionnaires were collected based on random sampling method from the three largest cities in Mauritania, namely, Nouakchott, Nouadibou, and Kiffa. Logistic regression analysis was performed to determine the critical factors influencing financial inclusion in Mauritania. The results highlight specific determinants affecting financial inclusion among the households in Mauritania (such as location, religious activities, financial cost, and financial literacy). The study recommends that these factors must be given due consideration in the efforts of increasing financial inclusion among the Mauritanians.